Food ration analysis of heavy labor and watch workers operating in extreme north weather conditions - Yermosh L. G.; Safronova T.N; Evtukhova O.M.; Kazina V.V (LLC Center for Information and Legal Support for the Development of the Arctic, 2018)
One of the most effective and cost-effective measures to increase human resilience to adverse environmental and labor factors is the correction of rations of northerners through the use of products of enhanced nutritional value and widespread use of local raw materials in food products. The article provides an analysis of the nutritional value of a two-week menu of employees of one of the mining enterprises in the North-Yeniseisk district of the Krasnoyarsk. The results of the research can serve as a basis for the development of corrective nutrition for workers of heavy labor on a rotational basis in the northern and Arctic regions of Russia.